2019
DOI: 10.1210/js.2019-00226
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-Secreting Tumors in Pediatric Patients With Cyanotic Congenital Heart Disease

Abstract: Catecholamine-secreting tumors are rare among the pediatric population but are increasingly being reported in children with sustained hypoxia secondary to cyanotic congenital heart disease (CCHD). With this review, we report the clinical characteristics of these tumors in children with CCHD. The articles included in the present review were identified using PubMed through February 2019. A manual search of the references retrieved from relevant articles was also performed. Pheochromocytomas and paragangliomas (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In patients with cyanotic malformations, it may be worth screening for renal impairment, pheochromocytoma, and paraganglioma. 400 Urinalysis, blood glucose levels, hematocrit, lipid panel, basic metabolic panel, and calcium levels are informative. Sarcopenia is not rare in ACHD.…”
Section: B) Management (Table 21)mentioning
confidence: 99%
“…In patients with cyanotic malformations, it may be worth screening for renal impairment, pheochromocytoma, and paraganglioma. 400 Urinalysis, blood glucose levels, hematocrit, lipid panel, basic metabolic panel, and calcium levels are informative. Sarcopenia is not rare in ACHD.…”
Section: B) Management (Table 21)mentioning
confidence: 99%
“…Recently, mutations in SDHA ( 21 ) and SDHAF2 were also identified in hereditary PHEOs and PGLs ( 40 ). In addition, multiple reports have shown that these tumors have high incidence in patients with cyanotic congenital heart disease ( 41 43 ).…”
Section: Sdh-deficient Paragangliomas and Pheochromocytomasmentioning
confidence: 99%
“…Patients with congenital heart disease (CHD) are known to be at increased risk of cancer [23][24][25]51]. Explanations include shared genetic and environmental risk factors, altered blood flow and hypoxia resulting from the disease itself or surgery such as Fontan's procedure [52,53], as well as radiation exposure. If the underlying disease is associated with both increased risk of cancer and increased radiation exposure, the dose/risk relationship may be confounded (Figure 2).…”
Section: Epidemiological Analysismentioning
confidence: 99%